Organic agriculture exploratory analisis of the research field in Iberoamerica (2021)
The research on the techniques, production and distribution on organic agriculture has acquired special relevance in the last decades. The preservation of the soil, human health, the increasing demand for these kinds of products along to the revenues that they generate are some of the main causes of this rapid scientific evolution of the field. The objective of the present study is to analyze the production of the area of organic agriculture in Iberoamerica from 1980 to 2018. The data is retrieved from the Web of Science scientific database and results are presented in categories of authors, volume of articles, countries, institutions and research areas. Keywords: Organic agriculture, Bibliometry, Iberoamerica JEL Codes: Q1, Q15, Y1 Received: 22/07/2020.  Accepted: 08/01/2021.  Published: 01/06/2021.